Can Behaviorally Informed Urban Living Labs Foster the Energy Transition in Cities? - Della Valle, Nives; Gantioler, Sonja; Tomasi, Silvia (Frontiers in Sustainable Cities, 2021)
Identifying governance schemes that promote cooperation among urban stakeholders is a priority in a context where rapid urbanization poses multiple and complex challenges for ensuring the sustainability of cities. Smart cities offer promising governance approaches, especially in the framework of the concept of Urban Living Labs (ULLs), as an enabling environment for so-called user-centric co-creation processes. While embedding a potential to promote solutions that tackle the challenges of urbanization, especially in relation to the energy transition, it is not yet clear how ULLs can effectively involve all relevant actors nor the extent of their impact, especially regarding behaviors. The study first analyzes the interplay between the challenge of urban energy transition and local governance schemes. Then, it explores how findings from behavioral sciences can inform the design of ULLs to effectively promote active engagement in the urban energy transition. Finally, it reviews the theoretical findings in relation to the Urban Living Lab that has been taking shape in the city of Trento, Italy.